The Causes of Conflicts in the Contracting Processes on the Internet - Murad Saib Mahmood, Zana Ismael Aziz, Hallo Mohammed Salih Abdulsamad, (Opción, 2019)
The aim of this paper is to examine the causes of conflicts in the contracting processes on the Internet. The methodology used in this paper is pure library research focusing mainly on primary and secondary sources. As a result, the application of the principle of childhood and even some other types of contracts on the Internet has been considered as another problematic case of contracting on the websites. In conclusion, consumer protection in international contracts has become necessary, and that protection requires the development of consumer protection provisions, especially with regard to the terms and conditions of Internet sites.